Artificial intelligence in health and science: an introspection - Ricardo Maia Ferreira (Journal of Evidence-Based Healthcare, 2023)
INTRODUCTION: Whenever there has been a technological revolution, there have been advantages and disadvantages associated with it. Artificial intelligence is now going through this phase of uncertainty. There are groups that agree and embrace this new technology, and others that simply refuse to let it into our daily lives. OBJECTIVE: The purpose of this reflection will be to understand the advantages and disadvantages of the use of artificial intelligence in health and science.